Investigating the Impact of EMU8086 Emulator on Developing Positive Student Attitude Towards Assembly Language Programming - Mathur, R. (Journal of Engineering Education Transformations, 2025)
This article presents the findings of an experiment designed to explore whether the utilization of a teaching aid, in this case the emulator EMU8086, can positively influence the target undergraduate students’ attitude towards acquiring 8086 assembly language programming skills or not? Methods: Twenty-nine students participated in a one-day hands-on workshop. The sessions focused on 8086 assembly language programming using the EMU8086 emulator. All twenty-nine participants submitted pre- and post-workshop polls. For analyzing the pre- and post-workshop poll data, a matched-pair Wilcoxon signed-rank test was utilized. Results: The average confidence level of participants in their capability to create an assembly language program by themselves doubled from 1.7931 ± 0.1437 to 3.7586 ± 0.1071 (P = 4.68957E-21). The average confidence level of participants in the EMU8086’s capability to assist in learning 8086 assembly language programming increased from 2.6207 ± 0.1749 to 3.9655 ± 0.0782 (P = 4.34958E-11). The average participant interest in similar skill enhancement opportunities soared from 3.2759 ± 0.1395 to 4.6897 ± 0.0874 (P = 5.25141E-14). The average participant interest in the domain of embedded systems slightly increased from 4.3103 ± 0.1005 to 4.6897 ± 0.0874 (P = 0.000145533). Conclusions: The findings suggest that exposure to the EMU8086 emulator had a positive impact on participants’ attitude towards acquiring assembly language programming skills. Relevance: Identifying the factors that drive interest in the domain of embedded systems which may help attract a larger consortium of potential learners and even lower the dropout rate.